(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the article we explore key aspects related to ensuring the stability and sustainability of the economic system. We review modern approaches to measuring and ensuring economic security, highlighting the main formats and indicators. The article covers both theoretical and practical aspects of achieving sustainable economic development and provides recommendations for modern strategies for ensuring economic security.